Innovation and research by private agribusiness in India - Pray, Carl E.; Nagarajan, Latha (International Food Policy Research Institute, 2012)
Agricultural research and innovation has been a major source of agricultural growth in developing countries. Unlike most research on agricultural research and innovation which concentrated on the role of government research institutes and the international agricultural research centers of the Consultative Group for International Agricultural Research, this paper focuses on private sector research and innovation. It measures private research and innovation in India where agribusiness is making major investments in research and producing innovations that are extremely important to farmers. It also reviews Indian policies that influence research and innovation. This new data and policy analysis can provide India policy makers with a basis for policies that can strengthen the direction and impact of agricultural research and innovation in the future.